Schools and Classifications of Fiqh: A Guide to Understanding the Diversity of Islamic Law - Siti Purmini (Sean Institute, 2024)
The following is a refined abstract: This paper examines the various major schools of thought in Islamic jurisprudence and classifies the legal diversity that arises from the different interpretations between these schools of thought. This research traces the history and development of the four main Sunni schools of thought—Hanafi, Maliki, Shafi'i, and Hanbali—as well as the role of the Shia school of thought in the dynamics of Islamic law. Using a comparative approach and textual analysis, this paper explores how legal interpretation varies based on social, cultural and geographical contexts. Apart from that, this research also examines the influence of these schools of thought on contemporary legal practice in various regions. It is hoped that the findings from this research will provide in-depth insight for academics, legal practitioners, and Muslims in general in appreciating the complexity and richness of the fiqh tradition as an integral part of Islamic legal heritage.